Hepatic Ischemia and Reperfusion Injury in the Absence of Myeloid Cell-Derived COX-2 in Mice - Duarte, Sergio (Public Library of Science, 2014)
Cyclooxygenase-2 (COX-2) is a mediator of hepatic ischemia and reperfusion injury (IRI). While both global COX-2 deletion and pharmacologic COX-2 inhibition ameliorate liver IRI, the clinical use of COX-2 inhibitors has been linked to increased risks of heart attack and stroke. Therefore, a better understanding of the role of COX-2 in different cell types may lead to improved therapeutic strategies for hepatic IRI. Macrophages of myeloid origin are currently considered to be important sources of the COX-2 in damaged livers. Here, we used a Cox-2flox conditional knockout mouse (COX-2−M/−M) to examine the function of COX-2 expression in myeloid cells during liver IRI. COX-2−M/−M mice and their WT control littermates were subjected to partial liver ischemia followed by reperfusion. COX-2−M/−M macrophages did not express COX-2 upon lipopolysaccharide stimulation and COX-2−M/−M livers showed reduced levels of COX-2 protein post-IRI. Nevertheless, selective deletion of myeloid cell-derived COX-2 failed to ameliorate liver IRI; serum transaminases and histology were comparable in both COX-2−M/−M and WT mice. COX-2−M/−M livers, like WT livers, developed extensive necrosis, vascular congestion, leukocyte infiltration and matrix metalloproteinase-9 (MMP-9) expression post-reperfusion. In addition, myeloid COX-2 deletion led to a transient increase in IL-6 levels after hepatic reperfusion, when compared to controls. Administration of celecoxib, a selective COX-2 inhibitor, resulted in significantly improved liver function and histology in both COX-2−M/−M and WT mice post-reperfusion, providing evidence that COX-2-mediated liver IRI is caused by COX-2 derived from a source(s) other than myeloid cells. In conclusion, these results support the view that myeloid COX-2, including myeloid-macrophage COX-2, is not responsible for the hepatic IRI phenotype.